PENGARUH SUBSTITUSI TELUR KEONG MAS (Pomacea canaliculata L.) TERHADAP KADAR PROTEIN, KALSIUM DAN KALIUM PADA KUE BOLU - Kurniati, Wenny Dwi; Panjaitan, Petni Nauli Br.; Hardiansyah, Angga (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2024)
So far, golden snail eggs have not been widely used as a processed food ingredient. Meanwhile, golden snail eggs contain various minerals and nutrients including protein, calcium and potassium. Sponge cake is one of several processed snacks that are often consumed and liked by people in Indonesia. Sponge cake has a delicious taste and quite economical selling value. One way to use golden snail eggs is by substituting chicken eggs with golden snail eggs (Pomacea canaliculata L.) in sponge cakes. The aim of this research is to determine the results of organoleptic tests as well as the protein, calcium and potassium content of sponge cake substituted with golden snail eggs. This experimental research used a completely randomized design (CRD). Golden snail eggs can be used as an ingredient in making sponge cakes. There were 5 treatments carried out to substitute golden snail eggs, namely 0 g (A0), 15 g (A1), 25 g (A2), 35 g (A3) and 50 g (A4). First, the golden snail eggs are washed, mixed with chicken eggs, vanilla, granulated sugar and developer, then stirred until evenly mixed. After the dough has risen, add sweetened condensed milk, vegetable oil, water and wheat flour and stir until evenly mixed. The finished dough is put into a baking dish then steamed for 40 minutes until cooked. The organoleptic test results showed significant differences in taste and texture parameters. Sample A1 was preferred by panelists, with a score of color (4,07), aroma (3,63), taste (4,17), texture (3,77) and acceptability (3,90), and contained protein of 5,40%, calcium 409,77% and potassium 73,72%.